Sosialisasi Sistem Informasi Desa untuk Meningkatkan Pelayanan Terhadap Masyarakat (Desa Cerdas) dalam Pelayanan Administrasi Desa - Suhada, Sitti; Takdir, Rahman; Sunardi, Sunardi; Pakaya, Jemmy A; Yassin, Rochmad M Thohir; Lahinta, Agus; Latief, Mukhlisulfatih; Mulyanto, Arip; Rohandi, Manda; Bouty, Abd Aziz; Novian, Dian; Kadim, Ahmad Azhar; A, Hermila (Universitas Negeri Gorontalo, 2023)
At this time the population administration service mechanism at the West Kotabaru Village Office still uses conventional methods which causes the process of recording and making population administration to take quite a long time, frequent queues occur, uncertainty over the completion of delayed services in the following days also often occurs so that it has an impact on the emergence of costs that must be incurred by the community because more than one time to the place of service. The purpose of this study is to design population administration using information technology tools as the first step in developing a smart village. Use of information technology in the process of managing village administration becomes easier, faster and neatly recorded. By utilizing the Village Administration Information System, it is hoped that the administration process will be carried out population in terms of correspondence to be faster and more efficient. System Usage Village Administration Information aims to advance the village and society and make it successful government program. Improving services for managing village administration is the main goal for village officials. Use of computerized programs in services It is hoped that the management of population administration will facilitate the work of village officials